2018
DOI: 10.1097/qai.0000000000001586
|View full text |Cite
|
Sign up to set email alerts
|

Are HIV Seroconversions Among Young Men Who Have Sex With Men Associated With Social Network Proximity to Recently or Long-Term HIV-Infected Individuals?

Abstract: Debate remains as to the relative HIV transmission contributions from individuals who are recently HIV-infected and individuals who have long-term infections. In this study, we examine the relationship between new HIV seroconversions occurring among young black men who have sex with men and network proximity to recently or long-term HIV-infected individuals. A cohort of young black men who have sex with men (N = 618) was generated through respondent-driven sampling across 3 waves. A recent HIV infection was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Additionally, there was evidence that this relationship was partially mediated by the effect of social support on sexual risk behavior. One of the few prospective cohort studies reviewed found a direct relationship between social support and decreased seroconversion [34]. These findings are compelling because they reveal the influence of social support on HIV risk, as well as suggesting sexual risk behavior as a potential mechanism by which this effect operates.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, there was evidence that this relationship was partially mediated by the effect of social support on sexual risk behavior. One of the few prospective cohort studies reviewed found a direct relationship between social support and decreased seroconversion [34]. These findings are compelling because they reveal the influence of social support on HIV risk, as well as suggesting sexual risk behavior as a potential mechanism by which this effect operates.…”
Section: Discussionmentioning
confidence: 91%
“…Morgan et al [34] investigated the effects that differences in HIV transmissibility among network members plays in HIV risk, a concept known as network viral load. This prospective cohort study exploring network factors and HIV found that for young BMSM in Chicago, each additional recently infected HIV positive partner (high transmissibility) in one's network was associated with 13 times greater odds of seroconversion during the study period.…”
Section: Network Viral Loadmentioning
confidence: 99%
“…Our analysis also likely underestimates total benefits received from all the HIV screening programmes because it does not evaluate the effect of re‐engaging those lost to HIV care [33]. Poor retention is both detrimental to those HIV‐infected and to preventing future transmission.…”
Section: Discussionmentioning
confidence: 99%
“…HIV incidence over the study period was 9.6% (characteristics associated with seroconversion were published previously). (38) The retention analysis revealed that those who were not retained were less likely to be HIV positive via both self-report and via laboratory testing (p=0.01 and .p=0.004), more likely to be straight or "other" sexual orientation (p= 0.02) and were slightly younger, median 21 years (IQR 19-24) vs. 23 years (IQR 21-25) (p=0.0001) at baseline. These measures were controlled for in the multivariate analyses.…”
Section: Baseline Demographics and Hiv Serostatusmentioning
confidence: 95%